La construction discursive de l’ethos numérique féminin. Cas des commentaires de la page Facebook « femmes insoumises algériennes » - Amel Zohra Hayat Mostefai; Kamila Oulebsir Oukil (Multilinguales)
Digital social networks (SNN) are a space for virtual exchange and sharing, which quickly became a space for denunciation and activism during the Hirak or Smile Revolution. This article aims to study the construction of the digital female collective ethos. It will be about an argumentative-stating analysis of the comments of a post or post on the Facebook page « femmes insoumises algériennes », reporting the participation of Algerian women in the protest movement. We propose to report on how the enunciative and argumentative processes, deployed in the comments and participating in the construction of the Algerian female collective ethos, play on the doxa and the collective social representations, in favor of or against the woman.